Pendidikan Politik bagi Gen Z dalam Menyongsong Pemilukada Tahun 2024 di Kabupaten Merauke - Eko Rachmat Saputro; Aenal Fuad Adam; Umiyati Haris (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Political education has a strategic role in increasing the participation of the younger generation, especially Generation Z (Gen Z), in the democratic process. This service activity aims to increase the awareness and understanding of Gen Z politics in Merauke Regency ahead of the 2024 Regional Head General Election (Pemilukada). The methods used include interactive lectures based on the results of the Gen Z political participation survey and Focus Group Discussion (FGD) which is divided into six discussion groups. The lecture aims to provide an overview of the conditions of political participation, while the FGD encourages participants to delve into local political issues and formulate strategic recommendations. The results of the activity showed a significant increase in participants' understanding of the democratic process, the mechanism of Pemilukada, and the importance of active participation in voting. Participants were also able to identify challenges to political participation, such as the influence of misinformation and apathy, as well as provide innovative proposals, such as the use of social media as a political education tool. This active participation-based approach is in line with the theory of political participation and deliberative democracy, which emphasizes the importance of rational discussion to strengthen the legitimacy of democracy. This activity concluded that political education designed contextually and interactively is effective in preparing Gen Z to play an active role in Pemilukada. Similar programs need to be continued on an ongoing basis to strengthen the political awareness of the younger generation and improve the quality of democracy at the local level. By harnessing the potential of digital technology and participatory approaches, political education can be a catalyst in building a generation of critical, intelligent, and responsible voters.